A study to determine the contribution to right ventricle stroke volume from pulmonary and tricuspid valve displacement volumes. (8th May 2014) - Jorstig, Stina; Emilsson, Kent; Lidén, Mats; Thunberg, Per
Summary Background Describing the systolic function of the right ventricle (RV) is a difficult task due to the complex shape and orientation of the RV. The purpose of this study was to investigate the extent to which the volumes encompassed by the pulmonary and tricuspid valve displacements contribute to the total right ventricle stroke volume (RVSV). Methods Twelve healthy volunteers were examined using cardiac magnetic resonance (CMR). Two series of time‐resolved axially rotated MR images were acquired that encompassed the tricuspid valve and the pulmonary valve, respectively. The volume related to each valve movement, the tricuspid plane displacement (TPD) and the pulmonary plane displacement (PPD), was determined by delineation in diastole and systole. These volumes, RVSVTPD and RVSVPPD, were compared to the stroke volume to determine the contributions to the total stroke volume from the TPD and the PPD. The remaining volume of the total RVSV was referred to as RVSVOther. An initial in vitro study was carried out to validate the accuracy of volume measurements using axially rotated images. Results In vitro measurements indicated that the method for volumetric measurements using axially rotated images was a very accurate one, with a mean difference of 0·04 ± 0·10 ml. The in vivo measurements of RVSVTPD, RVSVPPD and RVSVOther were 45 ± 10%, 13 ± 2% and 42 ± 11%, respectively. Conclusions Right ventricle stroke volume is determined by different individual volume changes as follows: RVSVTPD together with RVSVOther contributes to almost the entire RVSV in nearly equal proportions, while RVSVPPD contributes only a small amount and is approximately 30% of either RVSVTPD or RVSVOther.